2024
DOI: 10.1371/journal.ppat.1011939
|View full text |Cite
|
Sign up to set email alerts
|

Germinal center cytokine driven epigenetic control of Epstein-Barr virus latency gene expression

Yifei Liao,
Jinjie Yan,
Nina R. Beri
et al.

Abstract: Epstein-Barr virus (EBV) persistently infects 95% of adults worldwide and is associated with multiple human lymphomas that express characteristic EBV latency programs used by the virus to navigate the B-cell compartment. Upon primary infection, the EBV latency III program, comprised of six Epstein-Barr Nuclear Antigens (EBNA) and two Latent Membrane Protein (LMP) antigens, drives infected B-cells into germinal center (GC). By incompletely understood mechanisms, GC microenvironmental cues trigger the EBV genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 114 publications
0
1
0
Order By: Relevance
“…One possibility explaining this novel result is that a subset of the most dividing CD8+ T cells is more susceptible to the epigenetic modifications induced by IL-15 signaling and result in the silencing the gene(s) coding for the CD8β chain(s). This view is not unlikely since a recent study has shown that IL- 15, via STAT3 and STAT5 signaling, mediated silencing of Epstein-Barr Nuclear Antigens (EBNA) via epigenetic effects ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility explaining this novel result is that a subset of the most dividing CD8+ T cells is more susceptible to the epigenetic modifications induced by IL-15 signaling and result in the silencing the gene(s) coding for the CD8β chain(s). This view is not unlikely since a recent study has shown that IL- 15, via STAT3 and STAT5 signaling, mediated silencing of Epstein-Barr Nuclear Antigens (EBNA) via epigenetic effects ( 38 ).…”
Section: Discussionmentioning
confidence: 99%